(untitled) (Revista de Ciências Agroveterinárias, 2024)
This review article analyzes the legal regulation of organic production in Ukraine. The steady growth and development of this market are indicated by: 1) an increase in the area of agricultural land allocated for organic production, 2) a rise in the number of domestic organic operators, and 3) the increasing volume of organic product exports to other countries. However, there is a need to implement a set of measures, including: improving legal support, developing the infrastructure of the organic products market, ensuring adequate state support, and enhancing the system of standardization and certification for the production, processing, storage, and transportation of organic products. Additionally, there is a need to introduce an effective system for controlling the sale of organic raw materials, their processing, and the sale of organic products. A fundamental rethinking of the concept of food security in Ukraine is also required, particularly to determine the priority directions for developing agrarian policy under martial law conditions and in the post-war period.